Optical solitons of transmission equation of ultra-short optical pulse in parabolic law media with the aid of Backlund transformation - Al Qurashi, Maysaa' Mohamed; Baleanu, Dumitru; İnç, Mustafa (Elsevier Gmbh, Urban & Fischer Verlag, 2017)
The Backlund transformation is used to obtain optical soliton for a type of the Schrodinger equation. Kink-type and dark-optical soliton solutions are acquired of the Schrodinger equation. It is illustrated that the examined equation is integrable because if an equation has a Backlund transformation it could be integrable. Several constraint conditions for the parameters are derived that establish the existence of the soliton solutions. The numerical simulations supplement the analytical schemes. (C) 2017 Elsevier GmbH. All rights reserved.
Keywords: Backlund transformation; Schrodinger equation; Optical soliton